The politics of the global - Muppidi, Himadeep (Borderlines (Minneapolis, Minn.), 2004)
Refusing the false choice between objectivity and subjectivity, Himadeep Muppidi considers the production of the global as an intersubjective process that reveals the different political possibilities (e.g., colonial coercion, postcolonial ambivalence, and postcolonial co-option) opened by global relays of meanings, identity, and power. Muppidi concludes by exploring a variety of spaces and strategies for resisting the colonization of the global.